Impact of Pulmonary Hemodynamics and Ventricular Interdependence on Left Ventricular Diastolic Function in Children With Pulmonary Hypertension. (September 2016) - Burkett, Dale A.; Slorach, Cameron; Patel, Sonali S.; Redington, Andrew N.; Ivy, D. Dunbar; Mertens, Luc; Younoszai, Adel K.; Friedberg, Mark K.
Abstract : Background—: Through ventricular interdependence, pulmonary hypertension (PH) induces left ventricular (LV) dysfunction. We hypothesized that pediatric PH patients have LV diastolic dysfunction, related to adverse pulmonary hemodynamics, leftward septal shift, and prolonged right ventricular systole. Methods and Results—: Echocardiography was prospectively performed at 2 institutions in 54 pediatric PH patients during cardiac catheterization and in 54 matched controls. Diastolic LV measures including myocardial deformation were assessed by echocardiography. PH patients had evidence of LV diastolic dysfunction, most consistent with impaired LV relaxation, though some features of reduced ventricular compliance were present. PH patients demonstrated the following: reduced mitral E velocity and inflow duration, mitral E′ and E′ / A′, septal E′ and A′, pulmonary vein S and D wave velocities, and LV basal global early diastolic circumferential strain rate and increased mitral E deceleration time, LV isovolumic relaxation time, mitral E / E′, and pulmonary vein A wave duration. PH patients demonstrated leftward septal shift and prolonged right ventricular systole, both known to affect LV diastole. These changes were exacerbated in severe PH. There were no statistically significant differences in diastolic measures between patients with and without a shunt and minimal differences between patients with and without congenital heart disease. Multiple echocardiographic LV diastolic parameters demonstrated weak-to-moderate correlations with invasively determined PH severity, leftward septal shift, and prolonged right ventricular systole. Conclusions—: Pediatric PH patients exhibit LV diastolic dysfunction most consistent with impaired relaxation and reduced myocardial deformation, related to invasive hemodynamics, leftward septal shift, and prolonged right ventricular systole.